ANALISIS KETERAMPILAN MOTORIK KASAR PADA ANAK USIA SEKOLAH DASAR KELAS I DAN II DALAM KONTEKS PEMBELAJARAN PJOK DI SD NEGERI 1 PEJENG - I Ketut Ardiana Yoga; I Gede Suwiwa; Hendra Mashuri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the development of gross motor skills among first- and second-grade students in the context of Physical Education, Sports, and Health (PJOK) instruction. This study employs a quantitative, descriptive approach. The study sample consisted of 66 students, comprising all first- and second-grade students at SD Negeri 1 Pejeng. Total sampling was used as the sampling technique. The instrument used was the MOBAK 1–2 (Motorische Basiskompetenzen), which measures two domains: self-movement and object movement. Data collection was conducted through tests and direct observation, while data analysis utilized descriptive statistics, specifically means and percentages. The results of the study indicate that the development of students’ gross motor skills is generally in the “adequate” category, with a percentage of 42.4%. In the self-movement domain, balance had the highest mean score, while forward rolls had the lowest. In the object movement domain, catching demonstrated the highest achievement, while bouncing a ball had the lowest. These findings indicate that students’ gross motor development is not yet uniform across all skill aspects, particularly in skills requiring complex movement coordination. Based on the research findings, it was concluded that more varied and innovative physical education instruction, accompanied by systematic motor skill assessments, is necessary to optimally enhance students’ gross motor skill development.